The Effect of Marble-Based Educational Games on Early Literacy Skills in 5–6-Year-Old Children - Arifa An Nur An Nur; Azizah Amal; Sri Rika Amriani (BOCAH: Borneo Early Childhood Education and Humanity Journal, 2026)
This study examined the use of marble-based educational games in supporting the early literacy skills of children aged 5–6 years at TK Negeri Kelurahan Rangas. A quantitative quasi-experimental method with a non-equivalent control group design was used. The sample consisted of 40 children, with 20 children in the experimental group and 20 in the control group. The experimental group received Marble-based educational game treatment for six meetings, while the control group participated in regular literacy learning. Data were collected through tests, observation, and documentation, and analyzed using descriptive statistics, the Mann-Whitney U test, and normalized gain (N-Gain). The results showed that the experimental group’s mean score increased from 14.67 to 24.73, while the control group's increased from 13.87 to 19.13. The Mann-Whitney U test on post-test scores showed a significant difference between the two groups (p = 0.029). The N-Gain analysis also showed a higher improvement in the experimental group (M = 0.6805) than in the control group (M = 0.5465), with a significant difference between groups (U = 126.500, Z = -2.011, p = 0.044). Within the scope of this quasi-experimental, non-randomized design, marble-based educational games were associated with greater improvements in early literacy skills. Therefore, Marble can be considered a potential alternative medium for early literacy learning when used with appropriate teacher guidance.